Seasonality of tuberculosis among suspect patients visiting National Medical College, Teaching Hospital, Birgunj, Nepal - Shidiki, A; Pandit, BR; Bhargava, D; Mondal, S; Rijal, BP (Journal of Institute of Medicine Nepal, 2014)
Introduction: Seasonal variations of tuberculosis have been demonstrated in a number of studies with reported peaks in late winter and early spring or summer. The study was to analyze effect of seasonal variation on tuberculosis suspects across the calendar year. Methods: The research work was conducted in National Medical College & Teaching Hospital from January to December 2012. The sputum samples were collected and processed for acid fast bacilli from suspected tuberculosis patients. Results: Among 1403 suspected tuberculosis patients, 57.0% were male and 43.0% were females. 11.3% male and 4.0% female were present among the suspected cases of tuberculosis. The highest number of cases was in the age group 51-60.There was no any significant difference in between positive cases and age group (P=0.637). The positive cases of tuberculosis were found in 8.7% Muslim and 8.1% Hindu significant difference was not found in religion and tuberculosis (P=0.780%). The highest cases of tuberculosis was detected in June (14.9%) and to decline from august (13.2%) through December (4.4%). There was significant relation for cases and month (P=0.00001). More severe (3+) cases were found more (10.6%) in June, 2+ (4.4%) in July and 1+ (9.7%) in August which was statistically significant (P=0.00001). Conclusion: The seasonal variability of tuberculosis case detection showing mostly a peak in numbers in early spring and summer months.